2014
DOI: 10.1016/j.enbuild.2014.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Model predictive HVAC control with online occupancy model

Abstract: a b s t r a c tThis paper presents an occupancy-predicting control algorithm for heating, ventilation, and air conditioning (HVAC) systems in buildings. It incorporates the building's thermal properties, local weather predictions, and a self-tuning stochastic occupancy model to reduce energy consumption while maintaining occupant comfort. Contrasting with existing approaches, the occupancy model requires no manual training and adapts to changes in occupancy patterns during operation. A prediction-weighted cost… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Hailemariam, et al,2011 andSzczurek et al, 2017). Similarly, Mahdavi (2009), Dobbs andHencey (2014) and Oldewurtel et al (2013) have also extensively highlighted the importance of occupancy number as well as their behaviour in building energy consumption, building performance simulation and building control. Studies such as Erickson et al (2014) and Dong and Andrews (2009) have shown that around one-third of the energy consumed in the buildings can be saved using occupancy-based control.…”
Section: Introductionmentioning
confidence: 98%
“…Hailemariam, et al,2011 andSzczurek et al, 2017). Similarly, Mahdavi (2009), Dobbs andHencey (2014) and Oldewurtel et al (2013) have also extensively highlighted the importance of occupancy number as well as their behaviour in building energy consumption, building performance simulation and building control. Studies such as Erickson et al (2014) and Dong and Andrews (2009) have shown that around one-third of the energy consumed in the buildings can be saved using occupancy-based control.…”
Section: Introductionmentioning
confidence: 98%
“…Copyrights for third-party components of this work must be honored. For all other uses, contact the owner/author(s on occupant comfort [1,3,4]. Apart from time, occupancy can be skewed across space as well -i.e., different areas within a zone can have different occupancy levels at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…The results from the two studies were consistent and showed that measurements were sufficient for achieving energy savings around 50% in comparison to conventional controllers, while only small additional gains were provided through prognosis. Forecasts of indoor climate disturbances for control applications were also considered in [15] and [16], but with the focus on models for improving predictions. While [15] considered a self-tuning occupancy prediction model, [16] aimed to account for uncertainties in the control, and both investigations showed that their algorithms were beneficial.…”
Section: Introductionmentioning
confidence: 99%